2011
DOI: 10.1002/ejlt.201100037
|View full text |Cite
|
Sign up to set email alerts
|

Trans fatty acid isomers and the trans‐9/trans‐11 index in fat containing foods

Abstract: To determine trans fatty acid (TFA) distribution of contemporary foods, especially regarding individual trans octadecenoic acids (trans C18:1), 339 German foods of six categories (semi-solid fats, deep-fried potato products, bakery products, confectioneries, instant products and butter) were analysed using two GC methods. Results showed a high variation of TFA content between and within the categories containing between 0 and 40.5% of FAME except in butter, which is a source of natural TFA. The mean TFA values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
3
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 26 publications
1
74
3
2
Order By: Relevance
“…These reports suggested that hydrogenated fat could suppress diet-induced obesity. In this study, TFAs comprised 35.6 of total dietary FAs, and ELA, not vaccenic acid C18:1 trans-11 , was supposed to constitute the majority accurate figure not known of trans-formed C18:1 FA because industrial hydrogenation of vegetable oils produces ELA rather than vaccenic acid 25 . However, anti-obesity effects of TFAs that contained ELA were not observed in this study for the following reasons.…”
Section: Discussionmentioning
confidence: 82%
“…These reports suggested that hydrogenated fat could suppress diet-induced obesity. In this study, TFAs comprised 35.6 of total dietary FAs, and ELA, not vaccenic acid C18:1 trans-11 , was supposed to constitute the majority accurate figure not known of trans-formed C18:1 FA because industrial hydrogenation of vegetable oils produces ELA rather than vaccenic acid 25 . However, anti-obesity effects of TFAs that contained ELA were not observed in this study for the following reasons.…”
Section: Discussionmentioning
confidence: 82%
“…These foods are also cited as some of the main trans fat sources in the diet [59,60]. In this context, analyzing these foods can enable not only the inference of trans fat intake from Brazilian breads and cookies but also form the basis of a discussion about reducing the isomer in these products.…”
Section: Resultsmentioning
confidence: 99%
“…En aquellos aceites altamente insaturados, el tratamiento térmico induce isomerización de los áci-dos grasos linoleico y el linolénico hasta los AGT C18:1 (elaídico:t-9 y vaccénico:t-11) (25), ambos asociados con riesgo para ECV (26)(27). Se han reportado proporciones de AGT de 0,23-1,10% en aceite de girasol sometido a 200°C durante 40 minutos (28) cifran que incrementaron hasta 3,2% cuando se aumentó la temperatura del aceite a 250°C durante el mismo tiempo (29).…”
Section: Discussionunclassified